An m‐Health Intervention for Rheumatoid Arthritis in China ("Rheumatism Center" app): Study Protocol for a Prospective Randomized Controlled Trial. Issue 6 (22nd July 2021) - Luo, Huifang; Ma, Qing; Song, Jiating; Peng, Jie; Song, Yang; Chen, Guangxing; Lin, Changsong; Yang, Xiangwei
Abstract: Aim: To study the feasibility and effectiveness of a m‐Health app in improving the management of rheumatoid arthritis. Design: Randomized controlled trial. Methods: Sixty rheumatoid arthritis participants will be recruited for a 6‐month feasibility study. Patients meeting the inclusion criteria will be randomly allocated to receive standard care or standard care plus the m‐Health intervention. The primary outcome is the feasibility of a randomized controlled trial. In addition, we will investigate patient satisfaction in using the "Rheumatism Center" app in the intervention group. The secondary outcomes include the scores for the simplified disease activity index, clinical disease activity index, disease activity score 28, health assessment questionnaire and 6‐item self‐efficacy scale for chronic diseases. The assessments will be performed at baseline and at 4 weeks, 3 months and 6 months after the study is initiated. At the end of the study, we will also collect user views of the app through qualitative interviews. Results: This study is ongoing. The findings of this study will determine the feasibility and effectiveness of m‐Health intervention in the management of rheumatoid arthritis, hoping to enhance the awareness of disease management and quality of life for rheumatoid arthritis patients.